نحو إستراتيجية فاعلة لتكريس قيم المواطنة - قاسي, سليمة (جامعة الوادي University of Eloued, 2018)
هدفت هذه الدراسة إلى التعرف على الإستراتيجية المنتهجة من طرف المدرسة الجزائرية لتكريس قيم المواطنة لدى الناشئة ، من خلال الكشف عن قيم المواطنة الواردة في مقررات التربية المدنية للمرحلة الابتدائية والآليات المتبعة في تنميتها ومدى تجسدها في سلوكاتهم، وتأسيسا لذلك جاءت هذه الدراسة التحليلية لمحتوى كتب التربية المدنية للمرحلة الابتدائية بسنواتها الخمس،الموسومة بـ" نحو إستراتيجية فاعلة لتكريس قيم المواطنة لدى النشء في المناهج الدراسية الجزائرية"، محاولة الإجابة عن هذا التساؤل الذي نقدمه كمفتاح لمداخلتنا: ماهي إستراتيجية المدرسة الجزائرية لتكريس قيم المواطنة لدى النشء في المناهج الدراسية ؟. This study aims to identify the strategy adopted by the Algerian school to consolidate the values of citizenship in the youth, through revealing the values of citizenship contained in the curricula of civic education for the primary stage and the mechanisms used in their development and embodiment in their behavior. Hence, this analytical study of the textbook content of civic education for the primary stage in its five years, tagged " Towards an effective strategy to consolidate the values of citizenship among young people in the Algerian curriculum ".The problem of the study took shape in the question: What is the strategy of the Algerian school to consecrate the values of citizenship among young people? he study used the analytical descriptive method, where the content of the five curricula was analyzed; and extracting the values of citizenship included therein, the mechanisms used for their development, and the analysis of the data concluded to the following results: The civic education curriculum includes a set of values that aim to develop citizenship, belonging, identity, democracy, teamwork, rights, duties, law .... The civic education curriculum uses various mechanisms and methods to support the values of citizenship development, but these mechanisms are far from being embodied on the ground, making them absent in the behavior and practices of students.
لدى النشء في المناهج الدراسية الجزائرية
مقال
Keywords: المواطنة ; المناهج ; التربية المدنية ; المدرسة ; الابتدائية: Citizenship, Curriculum, Civic Education, Elementary Schoo